On The Consumer Attitude Analysis toward the Purchase Intention of Local Fashion Brand in Indonesia - Pertiwi, Ken Garudajati; Mayangsari, Lidia (Journal of Innovation, Business and Entrepreneurship, 2019)
Indonesia is one of the largest countries in the world, with the 4th largest population in the world. According to Badan Perancangan Pembangunan Nasional (BAPPENAS), the total population of Indonesia in 2018 is 265 million. With a large amount of population, it makes Indonesia has a large level of consumption, including the consumption level for clothing product, because clothing is one of the primary needs for every human being. So, with a large amount of population, the demand for clothing product is also high and always increasing, which this situation will become a great opportunity to run a business in the fashion industry.Currently, the creative industry in Indonesia is experiencing rapid development; one of the examples is in the fashion industry. The Creative Economy Agency of Indonesia (BEKRAF), states that Indonesia will become one of the world's fashion centers in 2025. For that, to be able to compete and survive in this industrial competition, the criteria of product required to be excellent physically or non-physically. Besides, being able to understand consumer behaviour for a product is needed to be able to compete in the fashion industry.This study aims to understand the consumer attitude towards the purchase Intention of Indonesians local fashion brands, especially in Bandung, Jakarta, Malang, and Surabaya. For make a better strategy in marketing activities, it will be beneficial for local brand owners to understand consumer attitude toward local fashion brands. The output of this research will be used to recommend the right marketing strategy for SMEs in Indonesian local fashion brand, especially for the LOOKOUT Indonesia brand.An online questionnaire collected this research with 206 respondents aged 17-35 years who live in Bandung, Jakarta, Malang and Surabaya. This data has passed five classic assumptions tests and then analyzed by multiple linear regression. This method is to find out the relationship that influence between consumer attitude towards local fashion brands to purchase intention. Also, cluster analysis tests have been conducted to determine differences in consumer attitude towards local fashion brands in each region in Bandung, Jakarta, Malang and SurabayaKeyword: Customer attitude, Purchase intention, Consumer buying behavior, Geographical Marketing, Local Fashion Brand